2011
DOI: 10.1097/id.0b013e31822608f4
|View full text |Cite
|
Sign up to set email alerts
|

Human Mandibular Trabecular Bone Density Correlation With Mechanical Strength: Implications for Implant Dentistry

Abstract: There was strong correlation of bone strength, bone mineral, and bone density by QCT. QCT is an excellent preoperative diagnostic tool to select the most mechanically appropriate implant for initial stability and improve the survival prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(4 reference statements)
1
7
0
Order By: Relevance
“…Previous publications demonstrate a positive correlation between BMD and bone quality 18–20 . Thus, mandibular body BMD may be important for the success of many dental procedures such as distraction osteogenesis, osteotomies, and hard‐tissue grafting.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications demonstrate a positive correlation between BMD and bone quality 18–20 . Thus, mandibular body BMD may be important for the success of many dental procedures such as distraction osteogenesis, osteotomies, and hard‐tissue grafting.…”
Section: Discussionmentioning
confidence: 99%
“…The micromotor allows measurement of Cm values between 0 and 35 Ncm, corresponding to a bone density varying from 0 to 1.33 g/cm 3 according to the formula provided by Di Stefano and colleagues, that is, bone density = ([Cm + 10.19]/33.95) g/cm 3 . This interval covers the range of bone‐density values found in the two arches . This study concerns patients whose Cm readings at all implant sites were ≤ 5 Ncm, that is, bone density at their implant sites was ≤ 0.45 g/cm 3 .…”
Section: Methodsmentioning
confidence: 99%
“…The probe depth was also recorded, given the fact that This interval covers the range of bone-density values found in the two arches. 35,36 This study concerns patients whose Cm readings at all implant sites were 5 Ncm, that is, bone density at their implant sites was 0.45 g/cm 3 Sutures were removed after 10 days. Depending upon individual patient needs, rehabilitation was achieved using single crowns or fixed prostheses, following delayed loading protocols, as defined by Aparicio and colleagues.…”
Section: Surgical and Implant-placement Protocolmentioning
confidence: 99%
“…In addition, the densities of the artificial bone were selected to correspond to the densities of the jaw bones. Devlin et al reported bone densities of 0.55, 0.31 and 1.11 g/cm 3 for the anterior maxilla, posterior maxilla and mandible [ 25 ], respectively; Choel et al reported the densities of the dental mandible and edentulous mandible to be 0.60 and 0.52 g/cm 3 [ 26 ], respectively; and Kido et al reported the densities of the anterior, premolar and molar regions to be 0.63, 0.57 and 0.52 g/cm 3 , respectively [ 27 ]. The artificial bone used in this study was made of a polyurethane material in accordance with the ASTM F1839-08 standard [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The artificial bone used herein was made of polyurethane material, according to the ASTM F1839-08 standards. The density of the artificial bone was selected to coincide with the density of the jaw bone [ 26 , 27 , 28 ]; therefore, Grades 50, 40 and 30 bones were selected as their densities are closest to that of jaw bones [ 29 ].…”
Section: Methodsmentioning
confidence: 99%